Heat exchange tube with microporous coating and groove surface and application of heat exchange tube
By processing microporous coatings and grooves on the surface of the heat exchange tube, combined with the use of modified graphene oxide and silane coupling agent, the shortcomings in the heat transfer coefficient, corrosion resistance and porosity of the existing heat exchange tubes are solved. , achieving efficient, energy-saving and environmentally friendly heat exchange effects.
Patent Information
- Application Number
- CN202411474352.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-14
AI Technical Summary
The existing heat exchange pipes have shortcomings in terms of heat transfer coefficient, corrosion resistance and porosity, which are difficult to meet the needs of modern industry for efficient, energy-saving and environmentally friendly heat exchange equipment.
A heat exchange tube with a microporous coating and a groove surface is used. The preparation method includes processing grooves on the surface of the base tube, removing dust and grease, configuring coating slurry and performing heat treatment. The coating slurry consists of a specific proportion of metal powder, pore-forming materials, adhesives and organic solvents. The performance of the microporous layer is optimized by the use of modified graphene oxide and silane coupling agents.
It realizes the high heat transfer coefficient, strong corrosion resistance and appropriate porosity of the heat exchange tube, extends the service life of the heat exchange tube, and meets the modern industry's demand for efficient, energy-saving and environmentally friendly heat exchange equipment.
Smart Images

Figure BDA0005095629360000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heat exchange, and in particular relates to a heat exchange tube with a microporous coating and a groove surface and an application thereof. Background Art
[0002] With the development of modern science and technology and industrialized production, energy conservation and consumption reduction have become the main control indicators of production departments in various industries. Industries such as petroleum and chemical industry account for a large proportion of the national economy. How to reduce energy consumption and investment costs in these industries has always been a key research topic in the industry. Shell and tube heat exchangers have always been the main and practical heat exchange equipment in these industries.
[0003] Traditional heat exchange tubes mainly exchange heat with fluids through their smooth surfaces, and their heat transfer efficiency is limited. Especially under high-load operating conditions, their heat transfer performance often cannot meet actual needs. In some corrosive media, traditional heat exchange tubes have weak corrosion resistance, and long-term use can easily lead to tube wall corrosion, affecting the heat transfer effect, and even causing the heat exchange tube to fail, affecting the life of the heat exchange tube. Later, people used machining methods, etching, and thermal spraying methods to process a surface with a microporous structure that can enhance heat transfer on the surface of the heat exchange tube. However, these methods all have shortcomings in the preparation process. The number of holes that can be provided by the machining method is relatively low. The environmental protection requirements and manufacturing costs of etching are high, and it is difficult to form connected holes. The porosity of the thermal spraying method is relatively low.
[0004] Therefore, the present invention proposes a heat exchange tube with a microporous coating and a grooved surface, aiming to solve the problems of existing heat exchange tubes in terms of heat transfer coefficient, corrosion resistance, porosity, etc. through innovative design and technical means, so as to meet the needs of modern industry for efficient, energy-saving and environmentally friendly heat exchange equipment. Summary of the invention
[0005] The purpose of the present invention is to provide a heat exchange tube with a microporous coating and a grooved surface, wherein the heat exchange tube has an appropriate surface porosity and a stable structure, a high heat transfer coefficient, strong corrosion resistance, and a long service life, thereby meeting the needs of modern industry for efficient, energy-saving, and environmentally friendly heat exchange equipment.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The preparation method of the heat exchange tube with microporous coating and groove surface comprises the following steps:
[0008] S1. Processing grooves on the surface of the base tube;
[0009] S2. Remove dust and grease from the surface of the base tube;
[0010] S3, preparing coating slurry;
[0011] S4. Apply the coating slurry on the surface of the base tube and perform heat treatment to obtain a heat exchange tube with a microporous coating and a grooved surface.
[0012] Preferably, the base tube is made of any one of stainless steel, copper, copper alloy, aluminum and aluminum alloy.
[0013] The raw materials for preparing the coating slurry include, by weight, 75 to 90 parts of metal powder, 5 to 15 parts of pore-forming material, 2 to 8 parts of adhesive, and 4 to 8 parts of organic solvent.
[0014] Preferably, the metal powder is one or more of stainless steel powder, copper powder, aluminum powder, nickel powder, tin powder, and zinc powder; more preferably, it is copper powder, nickel powder, tin powder, and zinc powder.
[0015] Preferably, the mass fraction of the copper powder accounts for 60% to 70% of the total mass of the metal powder.
[0016] Preferably, the mass ratio of the nickel powder, tin powder and zinc powder is (4-6):(8-12):1; more preferably, it is 5:10:1.
[0017] The inventors found that the use of four metal powders in a specific ratio as microporous layer materials can improve the thermal conductivity and corrosion resistance of the heat exchange tube. This may be because on the one hand, each metal powder has unique performance advantages, the thermal conductivity and electrical conductivity of copper, the high strength and corrosion resistance of nickel, the strengthening effect of tin, and the hardness and wear resistance of zinc. These properties complement each other in the alloy to form a more comprehensive and superior microporous layer material for heat exchange tubes. On the other hand, the addition of different metal powders can affect the phase structure and microstructure of the alloy, thereby optimizing the overall performance of the material. The alloying of nickel and copper can form a solid solution, improve the strength and corrosion resistance of the material; the addition of tin can further adjust the phase structure and improve the stability and durability of the material; the synergy of tin powder and zinc powder not only helps to form a more uniform and dense pore structure, thereby improving the heat exchange efficiency, enhancing the mechanical strength and durability of the material, but also can reduce the heat treatment temperature of the microporous layer, achieving the effect of saving energy and saving costs. Although excessive copper powder will improve the thermal conductivity of the heat exchange tube, the mechanical strength and corrosion resistance will be relatively weakened, thereby affecting the comprehensive performance of the heat exchange tube. Insufficient nickel powder will reduce the strength and corrosion resistance of the material, making the heat exchange tube easily damaged under harsh environmental conditions. Insufficient tin powder may cause the pore structure of the material to be uneven or not dense enough, reducing the heat exchange efficiency. The lack of zinc affects the corrosion resistance of the material and shortens the service life of the heat exchange tube.
[0018] Preferably, the particle size of the metal powder is 300-600 mesh.
[0019] The preparation method of the pore-forming material comprises the following steps:
[0020] A1, taking modified graphene oxide and dispersing it in N,N-dimethylformamide by ultrasonication to obtain a dispersion;
[0021] A2. Place PLA in N,N-dimethylformamide, and dissolve under stirring at 25-35°C for 2-4 hours to obtain a PLA solution.
[0022] A3. Add the dispersion dropwise into the PLA solution, heat to 40-45°C, continue stirring for 10-15 hours, and then vacuum dry to obtain the product.
[0023] The inventors found that the pore-forming material prepared by the method described in the present invention is selected and applied to the preparation of the microporous layer, which can enhance the strength and corrosion resistance of the heat exchange tube while improving the heat exchange efficiency. This may be because polylactic acid and graphene oxide work synergistically. On the one hand, the graphene oxide layer can form an effective heat conduction channel to accelerate the transfer of heat inside the material. At the same time, the porous structure of polylactic acid increases the heat exchange area, which is conducive to the faster exchange of heat through the surface of the material. On the other hand, polylactic acid, as a matrix material, provides good flexibility and processing performance. Graphene oxide, with its lamellar structure and high specific surface area, forms an effective dispersion and support in the polylactic acid matrix. This structural strengthening effect enables the composite material to disperse stress more evenly when subjected to force, thereby improving the overall strength and toughness of the material. In addition, the chemical properties of polylactic acid are relatively stable, and when graphene oxide is added to polylactic acid and forms a microporous layer, not only can its sheet structure effectively prevent corrosive substances in the fluid from directly contacting the polylactic acid matrix, thereby slowing down or preventing the corrosion process and enhancing corrosion resistance, but it can also form good chemical bonds with raw materials such as polylactic acid, further improving the stability and durability of the pores. At the same time, polylactic acid is a bio-based, degradable, non-toxic and harmless environmentally friendly polymer material, and using it as a raw material for the microporous layer has certain environmental significance.
[0024] Preferably, the molecular weight of the polylactic acid is 60,000 Da, and is purchased from Merck Chemical.
[0025] Preferably, the added amount of the modified graphene oxide is 0.1% to 0.5% of the mass of the polylactic acid.
[0026] Preferably, the volumes of N,N-dimethylformamide used in step A1 and step A2 are the same.
[0027] Preferably, in step A2, the mass ratio of polylactic acid to N,N-dimethylformamide is 1:(20-30).
[0028] Preferably, the preparation method of the modified graphene oxide comprises the following steps: dispersing graphene oxide in an ethanol aqueous solution, adding a silane coupling agent, reacting at 80 to 90° C. for 6 to 8 hours, cooling to room temperature, centrifuging, washing with ethanol and water in sequence, and drying to obtain the modified graphene oxide.
[0029] Preferably, the graphene oxide includes single-layer graphene oxide and multi-layer graphene oxide.
[0030] Preferably, the mass ratio of the single-layer graphene oxide to the multi-layer graphene oxide is (1-3):1; further preferably, it is 2:1.
[0031] Preferably, the single-layer graphene oxide includes a first single-layer graphene oxide and a second single-layer graphene oxide.
[0032] Preferably, the mass ratio of the first monolayer graphene oxide to the second monolayer graphene oxide is 1:(0.5-2); further preferably, it is 1:1.
[0033] Preferably, the first single-layer graphene oxide has an average thickness of 0.5 to 1.2 nm and a diameter of 4 to 7 μm.
[0034] Preferably, the second single-layer graphene oxide has an average thickness of 0.8 to 1.2 nm and a diameter of 0.5 to 5 μm.
[0035] Preferably, the multilayer graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers.
[0036] In some preferred schemes, the first monolayer graphene oxide and the multilayer graphene oxide are both purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; the second monolayer graphene oxide is purchased from Jiangsu Xianfeng Nano Materials Technology Co., Ltd.
[0037] The inventors found that the use of graphene oxide with different particle sizes can improve the heat transfer efficiency of the heat exchange tube while improving its durability and stability. This may be because on the one hand, graphene oxide with different particle sizes can form more complex and diverse pore structures, which include large pores, medium pores and small pores, which can accommodate fluid molecules of different sizes, increase the contact area between the fluid and the heat exchange tube wall, and thus improve the thermal conductivity and heat exchange rate of the heat exchange tube. On the other hand, the addition of graphene oxide can also enhance the binding force between the pore-forming material and the metal powder. This enhanced binding force helps prevent the metal powder from falling off or peeling off during long-term use, thereby improving the overall stability and durability of the heat exchange tube. In addition, the selected graphene oxide has both a multilayer structure and a single-layer structure. They have similar diameters and little difference in thickness. Therefore, there is a certain compatibility between the two. On the one hand, the complementarity in the number of layers is achieved, which not only retains the high activity of the single-layer graphene oxide, but also improves the mechanical properties of the microporous layer. On the other hand, the single-layer and multi-layer graphene oxides of similar sizes are intertwined and stacked to form a stable three-dimensional network structure, which can improve the structural stability of the microporous layer. However, the particle size of graphene oxide is too small and it is easy to agglomerate in the system, affecting the performance of the microporous layer.
[0038] Preferably, the mass ratio of the graphene oxide to the ethanol aqueous solution is 1:(15-25); further preferably, it is 1:20.
[0039] Preferably, the mass fraction of ethanol in the ethanol aqueous solution is 65% to 75%.
[0040] Preferably, the silane coupling agent is one or more of γ-glycidyloxypropyltrimethoxysilane, γ-divinyltriaminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, vinylmethyldimethyloxysilane, and vinyltriethoxysilane; further preferably, it is γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, and γ-mercaptopropyltriethoxysilane.
[0041] Preferably, the mass ratio of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane and γ-mercaptopropyltriethoxysilane is 1:(0.5-2):(1-3); more preferably, it is 1:1:2.
[0042] The inventors found that the use of a specific silane coupling agent to modify graphene oxide can improve the dispersibility of graphene oxide in the system, thereby improving the performance of the heat exchange tube. This may be because on the one hand, the polar groups (such as hydroxyl, carboxyl, etc.) on the surface of graphene oxide react chemically with the active groups of the coupling agent to form stable chemical bonding, thereby reducing the surface energy of graphene oxide, making it easier to disperse in a solvent or polymer. One end of the silane coupling agent reacts chemically with graphene oxide, and the other end has a functional group compatible with the polymer matrix. This structure enables better interface bonding to be formed between graphene oxide and the polymer matrix, improves the compatibility of the two, further improves the stability and dispersibility of graphene oxide in the system, thereby improving the performance of the pore-forming material and the microporous layer. On the other hand, carbon-carbon double bonds are grafted onto graphene oxide through modification with silane coupling agent, which can undergo cross-linking reaction with polymers such as polylactic acid, thereby further improving the bonding force between graphene oxide and the polymer, thereby improving the stability of the pores and ensuring the thermal conductivity coefficient and stability of the heat exchange tube material.
[0043] Preferably, the added amount of the silane coupling agent is 5 to 10 times the mass of graphene oxide.
[0044] Preferably, the adhesive includes one or both of polyvinyl alcohol and polyethylene glycol.
[0045] Preferably, the viscosity of the polyvinyl alcohol is 3.2-3.6 cps, the alcoholysis degree is 87-89 mol%, and the ash content is ≤0.4%.
[0046] In some preferred embodiments, the polyvinyl alcohol is purchased from Kuraray of Japan, PVA-203.
[0047] Preferably, the organic solvent comprises acetone.
[0048] Preferably, the coating slurry has a coating thickness of 0.1 to 0.5 mm.
[0049] The specific method of bonding and curing is: using a vacuum heat treatment furnace, first heating to 350-450°C at a rate of 4-6°C / min, keeping warm for 12-17 minutes, then heating to 950-1000°C at a rate of 8-12°C / min, keeping warm for 30-40 minutes, and quickly cooling to room temperature.
[0050] Preferably, the vacuum degree of the vacuum heat treatment furnace is (4-6)×10 -3 Pa.
[0051] The inventors found that before the temperature is increased to the low temperature stage, the various properties of the microporous layer can be improved by first increasing the temperature to the low temperature stage at a lower rate. This may be because the adhesive can be volatilized by a lower temperature increase rate and the low temperature stage can avoid the collapse of the coating skeleton and thus affect the pore structure. If the temperature is increased too fast in this stage, it will cause boiling, and if it is too slow, it will cause the coating layer to flow, affecting the thickness and performance of the final microporous layer.
[0052] In some preferred schemes, the pore-forming material needs to be added in an appropriate amount. The more pore-forming agent is used, the higher the porosity is. However, too much pore-forming agent may reduce the strength and bonding force of the microporous layer.
[0053] In some preferred embodiments, before the microporous layer is formed, grooves can be machined on the surface of the heat exchange tube by mechanical processing or chemical etching. These grooves can increase the heat exchange area and improve the heat transfer efficiency. At the same time, the grooves can also play a role in disturbing the flow, promoting the turbulent flow of the fluid in the heat exchange tube, and further improving the heat transfer performance.
[0054] The heat exchange tube is used in the fields of chemical industry, petroleum, etc.
[0055] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0056] 1. The present invention provides a heat exchange tube with a microporous coating and a grooved surface. The heat exchange tube has an appropriate surface porosity and a stable structure. The heat exchange tube has a high heat transfer coefficient, strong corrosion resistance, and a long service life, meeting the needs of modern industry for efficient, energy-saving, and environmentally friendly heat exchange equipment.
[0057] 2. The present invention can improve the thermal conductivity and corrosion resistance of the heat exchange tube by selecting four metal powders in a specific ratio as the microporous layer material.
[0058] 3. The present invention selects the pore-forming material prepared by the method described in the present invention and applies it to prepare the microporous layer, which can improve the heat exchange efficiency of the heat exchange tube while enhancing its strength and corrosion resistance.
[0059] 4. The present invention can improve the heat exchange efficiency of the heat exchange tube while improving its durability and stability by selecting graphene oxide with different particle sizes.
[0060] 5. The present invention improves the dispersibility of graphene oxide in the system by selecting a specific silane coupling agent to modify graphene oxide, thereby improving the performance of the heat exchange tube.
[0061] 6. The present invention heats up to the low temperature stage at a relatively low heating rate for heat preservation before heating up to the high temperature stage, which can improve various properties of the microporous layer.
[0062] 7. The present invention processes grooves on the surface of the heat exchange tube before the microporous layer is formed. These grooves can increase the heat exchange area and improve the heat transfer efficiency. At the same time, the grooves can also promote the turbulent flow of the fluid in the heat exchange tube, further improving the heat transfer performance. DETAILED DESCRIPTION
[0063] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] The raw materials used in the present invention are all commercially available, specifically:
[0065] Polylactic acid, PLA, with a molecular weight of 60,000 Da, was purchased from Merck Chemicals.
[0066] The average thickness of the first monolayer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm; the average thickness of the second monolayer graphene oxide is 0.8-1.2 nm, and the diameter is 0.5-5 μm; both are purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.
[0067] The multilayer graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers, and was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0068] The viscosity of polyvinyl alcohol is 3.2-3.6 cps, the degree of alcoholysis is 87-89 mol%, and the ash content is ≤0.4%. It is purchased from Kuraray of Japan, PVA-203.
[0069] Example 1
[0070] This embodiment provides a heat exchange tube with a microporous coating and a grooved surface, and a preparation method thereof, comprising the following steps:
[0071] S1. Processing grooves on the surface of the base tube;
[0072] S2. Remove dust and grease from the surface of the base tube;
[0073] S3, preparing coating slurry;
[0074] S4. Apply the coating slurry on the surface of the base tube and perform heat treatment to obtain a heat exchange tube with a microporous coating and a grooved surface.
[0075] The base tube is made of stainless steel.
[0076] The raw materials for preparing the coating slurry include, by weight, 80 parts of metal powder, 10 parts of pore-forming material, 5 parts of adhesive, and 6 parts of organic solvent.
[0077] The metal powder is copper powder, nickel powder, tin powder and zinc powder.
[0078] The mass fraction of the copper powder accounts for 65% of the total mass of the metal powder.
[0079] The mass ratio of the nickel powder, tin powder and zinc powder is 5:10:1.
[0080] The particle size of the metal powder is 500 meshes.
[0081] The preparation method of the pore-forming material comprises the following steps:
[0082] A1, taking modified graphene oxide and dispersing it in N,N-dimethylformamide by ultrasonication to obtain a dispersion;
[0083] A2, PLA was placed in N,N-dimethylformamide, and dissolved in a sealed container at 30°C with stirring for 3 hours to obtain a PLA solution;
[0084] A3. Add the dispersion dropwise into the PLA solution, heat to 43°C and continue stirring for 13 hours, then vacuum dry to obtain the product.
[0085] The added amount of the modified graphene oxide is 0.3% of the mass of the polylactic acid.
[0086] The volume of N,N-dimethylformamide used in step A1 and step A2 is the same.
[0087] In the step A2, the mass ratio of polylactic acid PLA to N,N-dimethylformamide is 1:25.
[0088] The preparation method of the modified graphene oxide comprises the following steps: dispersing the graphene oxide in an ethanol aqueous solution, adding a silane coupling agent, reacting at 85° C. for 7 hours, cooling to room temperature, centrifuging, washing with ethanol and water in sequence, and drying to obtain the modified graphene oxide.
[0089] The graphene oxide is single-layer graphene oxide and multi-layer graphene oxide, and the mass ratio is 2:1.
[0090] The single-layer graphene oxide includes a first single-layer graphene oxide and a second single-layer graphene oxide, and the mass ratio of the first single-layer graphene oxide and the second single-layer graphene oxide is 1:1.
[0091] The mass ratio of the graphene oxide to the ethanol aqueous solution is 1:20.
[0092] The mass fraction of ethanol in the ethanol aqueous solution is 70%.
[0093] The silane coupling agent is γ-aminopropyltriethoxysilane, vinyltrimethoxysilane and γ-mercaptopropyltriethoxysilane, and the mass ratio is 1:1:2.
[0094] The added amount of the silane coupling agent is 8 times the mass of graphene oxide.
[0095] The adhesive is polyvinyl alcohol.
[0096] The organic solvent is acetone.
[0097] The coating slurry has a coating thickness of 0.4 mm.
[0098] The specific method of the heat treatment is: using a vacuum heat treatment furnace, first heating to 400°C at a rate of 5°C / min, keeping the temperature for 15 minutes, then heating to 980°C at a rate of 10°C / min, keeping the temperature for 35 minutes, and then quickly cooling to room temperature to obtain the product.
[0099] The vacuum degree of the vacuum heat treatment furnace is 5×10 -3 Pa.
[0100] Example 2
[0101] The difference between this embodiment and embodiment 1 is that the mass fraction of the copper powder accounts for 60% of the total mass of the metal powder.
[0102] Example 3
[0103] The difference between this embodiment and embodiment 1 is that the mass ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:1.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 1 is that the mass fraction of the copper powder accounts for 80% of the total mass of the metal powder.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 1 is that the mass ratio of the nickel powder, the tin powder and the zinc powder is 5:5:1.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 1 is that the pore-forming material is polylactic acid.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 1 is that the preparation method of the pore-forming material comprises the following steps:
[0112] A1, ultrasonically dispersing graphene oxide in N,N-dimethylformamide to obtain a dispersion;
[0113] A2. PLA was placed in N,N-dimethylformamide and dissolved in a sealed container at 30°C with stirring for 3 hours to obtain a PLA solution;
[0114] A3. Add the dispersion dropwise into the PLA solution, heat to 43°C and continue stirring for 13 hours, then vacuum dry to obtain the product.
[0115] Comparative Example 5
[0116] The difference between this comparative example and Example 1 is that the graphene oxide is a single-layer graphene oxide.
[0117] Comparative Example 6
[0118] The difference between this comparative example and Example 1 is that the first monolayer graphene oxide has an average thickness of 1 to 2 nm and a diameter of 10 to 20 μm, and is purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0119] Comparative Example 7
[0120] The difference between this comparative example and Example 1 is that the silane coupling agent is γ-aminopropyltriethoxysilane and γ-mercaptopropyltriethoxysilane, and the mass ratio is 1:2
[0121] Comparative Example 8
[0122] The difference between this comparative example and Example 1 is that the specific method of the heat treatment is: using a vacuum heat treatment furnace, heating to 980°C at a rate of 10°C / min, keeping the temperature for 35 minutes, and quickly cooling to room temperature to obtain the product.
[0123] Comparative Example 9
[0124] The difference between this comparative example and Example 1 is that the raw materials for preparing the coating slurry include, by weight, 80 parts of metal powder, 20 parts of pore-forming material, 5 parts of adhesive, and 6 parts of organic solvent.
[0125] Performance Testing
[0126] The heat transfer coefficient and porosity of the heat exchange tube were tested with reference to the method in the paper "Research on Heat Transfer Performance of Metal Fiber Porous Surface Heat Exchange Tube" published by Zhi Hao et al. The corrosion resistance of the microporous layer was tested with reference to the method in GB / T 1771-2007 "Determination of Neutral Salt Spray Resistance of Paints and Varnishes", and the corrosion resistance of the specimens was rated with reference to GB / T 6461-2002 "Rating of Test Specimens and Specimens of Metallic and Other Inorganic Coatings on Metal Substrates after Corrosion Tests", with a rating of 0 to 10, where the larger the number, the better the corrosion resistance. The results are shown in Table 1.
[0127] Table 1 Measurement results
[0128]
[0129] According to statistics, the heat exchange tubes prepared by Examples 1 to 3 of the present invention have a high heat transfer coefficient, a porosity between 50% and 60%, a suitable porosity, and high corrosion resistance. In Comparative Example 1, the proportion of copper powder is too large, in Comparative Example 2, the tin powder is too little, in Comparative Example 3, no modified graphene oxide is added, in Comparative Example 4, no graphene oxide is modified, in Comparative Example 5, no multilayer graphene oxide is added, in Comparative Example 6, the diameter of the first monolayer graphene oxide is too large, in Comparative Example 7, no vinyltrimethoxysilane is added, in Comparative Example 8, there is no low-temperature insulation section during heat treatment, in Comparative Example 9, excessive pore-forming material is added, and the heat transfer coefficient of the prepared heat exchange tube is low, the porosity does not meet the requirements, and the corrosion resistance is poor. Therefore, the heat exchange tube surface porosity prepared by the method described in this application is suitable and the structure is stable, the heat exchange tube has a high heat transfer coefficient, strong corrosion resistance, and a long life, which meets the needs of modern industry for efficient, energy-saving, and environmentally friendly heat exchange equipment.
[0130] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A heat exchange tube with a microporous coating and a grooved surface, characterized in that: The preparation method thereof comprises the following steps: S1. Processing grooves on the surface of the base tube; S2. Remove dust and grease from the surface of the base tube; S3, preparing coating slurry; S4, applying the coating slurry on the surface of the base tube and performing heat treatment to obtain a heat exchange tube with a microporous coating and a groove surface; The raw materials for preparing the coating slurry include, by weight, 75 to 90 parts of metal powder, 5 to 15 parts of pore-forming material, 2 to 8 parts of adhesive, and 4 to 8 parts of organic solvent; The metal powder is one or more of stainless steel powder, copper powder, aluminum powder, nickel powder, tin powder and zinc powder; The preparation method of the pore-forming material comprises the following steps: A1, taking modified graphene oxide and dispersing it in N,N-dimethylformamide by ultrasonication to obtain a dispersion; A2. Place PLA in N,N-dimethylformamide, and dissolve under stirring at 25-35°C for 2-4 hours to obtain a PLA solution. A3. Add the dispersion dropwise into the PLA solution, heat to 40-45°C, continue stirring for 10-15 hours, and then vacuum dry to obtain the product.
2. The heat exchange tube with microporous coating and groove surface according to claim 1, characterized in that: The mass fraction of the copper powder accounts for 60% to 70% of the total mass of the metal powder; the mass ratio of the nickel powder, tin powder and zinc powder is (4 to 6): (8 to 12):
1.
3. The heat exchange tube with microporous coating and groove surface according to claim 1, characterized in that: The added amount of the modified graphene oxide is 0.1% to 0.5% of the mass of the polylactic acid.
4. The heat exchange tube with microporous coating and groove surface according to claim 1, characterized in that: The preparation method of the modified graphene oxide comprises the following steps: dispersing the graphene oxide in an ethanol aqueous solution, adding a silane coupling agent, reacting at 80 to 90° C. for 6 to 8 hours, cooling to room temperature, centrifuging, washing with ethanol and water in sequence, and drying to obtain the modified graphene oxide.
5. The heat exchange tube with microporous coating and groove surface according to claim 4, characterized in that: The graphene oxide includes single-layer graphene oxide and multi-layer graphene oxide; the mass ratio of the single-layer graphene oxide to the multi-layer graphene oxide is (1-3):
1.
6. The heat exchange tube with microporous coating and groove surface according to claim 5, characterized in that: The single-layer graphene oxide includes a first single-layer graphene oxide and a second single-layer graphene oxide.
7. The heat exchange tube with microporous coating and groove surface according to claim 6, characterized in that: The first single-layer graphene oxide has an average thickness of 0.5 to 1.2 nm and a diameter of 4 to 7 μm; the second single-layer graphene oxide has an average thickness of 0.8 to 1.2 nm and a diameter of 0.5 to 5 μm.
8. The heat exchange tube with microporous coating and grooved surface according to claim 4, characterized in that: The silane coupling agent is one or more of γ-glycidyloxypropyltrimethoxysilane, γ-divinyltriaminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, vinylmethyldimethyloxysilane, and vinyltriethoxysilane.
9. A heat exchange tube prepared according to the heat exchange tube with microporous coating and grooved surface according to any one of claims 1 to 8.
10. An application of the heat exchange tube according to claim 9, characterized in that: Used in chemical, petroleum and energy fields.